Synthesis and characterization of Fe-Al alloy with different sintering temperature - Maimun Razali (Universiti Malaysia Perlis, 2008)
The iron aluminides Fe3Al and FeAl3 have been among the most widely studied intermetallics because of their low cost, low density, good wear resistance, ease of fabrication and resistance to oxidation and corrosion. A variety of fabrication methods have been employed in the study of intermetallic compound; powder metallurgy processing is becoming increasingly important for obtaining desirable microstructures, improved properties, and near net shape manufacturing capabilities. In this paper the comparison of physical and mechanical properties of Fe3Al and FeAl3 with different sintering temperature were studied. Powder metallurgy technique was used, which iron and aluminum powder were mixed together and compacted for three samples of Fe3Al and three samples of FeAl3. Each sample has the same composition value and same pressure value for compaction process. The sintering processes were done in three different sintering temperatures for Fe3Al samples which were 1050°C, 1000°C and 950°C and three different sintering temperatures for FeAl3 samples which were 500°C, 450°C and 400°C. With all different sintering temperature, the samples are expected to have different properties. All samples went through a few testing include linear shrinkage, density and porosity, Vickers Hardness testing, Scanning Electron Microscope (SEM), XRay Diffraction and Energy Dispersive X-ray analyses. A great amount of pores, brittle and easily broken characteristics with a relatively low melting temperature were observed in the FeAl3 sample. The Fe3Al sample which was sintered at 1050 °C exhibited significantly higher hardness and density.